(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2024)
Drawing on social movement studies (SMT), this article analyses the engagement of activists, citizens, informal organizations and groups against the genocide and war in Gaza. Using an empirical methodology that refers to 42 semi-structured interviews with students and activists who took part in street demonstrations and encampments in several universities in different localities in Europe, the United States, North Africa and the Middle East, the research aims to explore how antiwar protests were driven by a single issue, the struggle against the genocide in Gaza, showing a high degree of intersectionality with other demands, repressed with the censorship of protests. The research also explores the complex intertwining of violence and colonialism, focusing on the consequences of the occupation on Palestinian women.